2009
DOI: 10.1111/j.1755-6686.2009.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Needle‐stick Injury: A Novel Intervention to Reduce the Occupational Health and Safety Risk in the Haemodialysis Setting

Abstract: Needle-stick injury (NSI) is a major occupational health and safety issue facing healthcare professionals. The administration of erythropoiesis-stimulating agents (ESA) in haemodialysis patients represents a major cause for injections. The purpose of this initiative was to familiarise nursing staff with needle-free administration of an ESA in haemodialysis patients to reduce the risk of NSI. Epoetin beta comes in a commercial presentation with a detached needle. Epoetin beta was administered to 10 haemodialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…No needle stick injuries were reported, haemoglobin levels were maintained and the system was well accepted by the nursing staff (Chow et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…No needle stick injuries were reported, haemoglobin levels were maintained and the system was well accepted by the nursing staff (Chow et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, different studies have shown transmission of Hepatitis B and C from HCWs to patients ( Buster, van der Eijk, de Man, & Schalm, 2004 ; Laurenson et al, 2007 ; Lot et al, 2007 ; Raggam, Rossmann, Salzer, Stauber, & Kessler, 2009 ) and approximately 70 infected health care workers have been identified in transmitting their infection to patients ( Carlson & Perl, 2010 ). Hence significant health workers are exposed to blood borne pathogens that pose a threat to them as well as their patients, health ( Chow, Rayment, Wong, Jefferys, & Suranyi, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simulationbased healthcare education uses well-defined learning objectives and tasks with an appropriate level of difficulty [19]. Efforts to reduce occupational health and safety risks include staff education, safer equipment, and the reduction of needle-dependent procedures [20].…”
Section: Evaluation Using the Simulatormentioning
confidence: 99%